Comparison of dry sliding behavior and wear mechanism of low metallic and copper-free brake pads. (November 2020) - Tavangar, Reza; Moghadam, Hamid Ansari; Khavandi, Alireza; Banaeifar, Saeed
Abstract: Rising environmental concerns and implementing restrictions on the use of copper in friction materials (FM) make it mandatory for manufacturers to look for a reliable replacement. Two commercial pads: 1) low metallic FM contains 7 wt.% copper fibers and 2) low metallic FM contains thermal graphite (TG), and cellulose fibers as replacements for copper were studied. The two FMs showed almost identical thermal behavior. However, Cu-contained FM exhibited a bit more thermal stability. The fade ratio and recovery ratio in the first fade and recovery stages showed almost the same values. Moreover, in the second fade, change from 86% to 78% and second recovery change from 90% to 77%, respectively, for Cu-contained and Cu-Free FMs. Highlights: The frictional behavior of a copper-free and low-met commercialize friction composites is investigated. As substitutions for copper, thermo-graphite and cellulose fiber were used. Cellulose fiber at elevated temperature act as a pore generator leads to an improvement in fade resistance. Graphite and wear debris in C7 facilitate the formation of secondary contact plateaus. Both low-metallic and copper-free materials can be interchangeably used based on restrictions, code compliance, and economic issues.